Developing advanced literacy in first and second languages : meaning with power - Schleppegrell, Mary; Colombi, Cecilia (Lawrence Erlbaum Associates, 2002)
This book addresses the linguistic challenges faced by diverse populations of students at the secondary and post-secondary levels as they engage in academic tasks requiring advanced levels of reading and writing. It aims to contribute to research and pedagogy on advanced literacy development.
Includes papers presented at a conference held Feb. 2000, University of California, Davis.
Keywords: Literacy -- Study and teaching -- Congresses.; Language and languages -- Study and teaching -- Congresses.; Analphabétisme -- Étude et enseignement -- Congrès.; Langage et langues -- Étude et enseignement -- Congrès.; LANGUAGE ARTS & DISCIPLINES -- Literacy.; Language and languages -- Study and teaching; Literacy -- Study and teaching; Leesvaardigheid.; Conference papers and proceedings